Current Progress in Particle-Based Systems for Transdermal Vaccine Delivery - Pielenhofer, Jonas; Sohl, Julian; Windbergs, Maike; Langguth, Peter; Radsak, Markus P. (Frontiers in Immunology, 2020)
Transcutaneous immunization (TCI) via needle-free and non-invasive drug delivery systems is a promising approach to overcome current limitations of conventional parenteral vaccination methods. The targeted access to professional antigen presenting cell (APC) populations within the skin, such as Langerhans cells (LCs), various dermal dendritic cells (dDCs), macrophages and others makes the skin an ideal vaccination site to specifically shape immune responses as required. The stratum corneum (SC) of the skin is the main penetration barrier that needs to be overcome by the vaccine components in a coordinated way to achieve optimal access to dermal APC populations that induce priming of T cell or B cell responses for protective immunity. While there are numerous approaches to penetrate the SC, such as electroporation, sono- or iontophoresis, barrier and ablative methods, jet and powder injectors and microneedle mediated transport, we will focus this review on the recent progress made in particle-based systems for TCI. This particular approach delivers vaccine antigens together with adjuvants to perifollicular APCs by diffusion and deposition in hair follicles. Different delivery systems including nanoparticles and lipid-based systems, for example solid nano-emulsions, and their impact on immune cells and generation of a memory effect are discussed. Moreover, challenges for TCI including timely and targeted delivery of antigens and adjuvants to APCs within the skin as well as deeper understanding of ill-defined mechanisms leading to the induction of effective memory responses are addressed.